Information Technology and the Structuring of Organizations - Orlikowski, Wanda J.; Robey, Daniel (Information Systems Research, 1991)
Recent work in social theory departs from prior traditions in proposing that social phenomena can be understood as comprising both subjective and objective elements. We apply this premise of duality to understanding the relationship between information technology and organizations. We construct a theoretical framework in which the development and deployment of information technology in organizations is a social phenomenon, and in which the organizational consequences of technology are products of both material and social dimensions. The framework is based on Giddens' theory of structuration, and it allows us to progress beyond several of the false dichotomies (subjective vs objective, socially constructed vs material, macro vs micro, and qualitative vs quantitative) that persist in investigations of the interaction between organizations and information technology. The framework can be used to guide studies in two main areas of information systems research—systems development and the organizational consequences of using information technology.